2021
DOI: 10.1186/s12891-021-04662-2
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of ribosome-related genes in ankylosing spondylitis: a systems biology approach and experimental method

Abstract: Background Ankylosing spondylitis (AS) is an autoimmune rheumatic disease. Few candidate gene associations have been reported for AS and the current understanding of its pathogenesis remains still poor. Thus, the exact mechanism of AS is needed to urgently be disclosed. The purpose of this study was to identify candidate genes involving in AS disease. Methods and results GSE25101 publicly available microarray and GSE117769 RNA-seq datasets of AS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…Recent studies link ribosome protein mutations and abnormal ribosomes to poor prognosis, highlighting that ribosome protein targeted therapy is a promising treatment for cancer patients [ 11 ]. Ribosomal protein genes have the largest number of processed pseudogenes, approximately 1700; these genes include cyclophilin A, actin, keratin (keratin), GAPDH, cytochrome C (cytochrome C), and nucleophosmin [ 12 ]. There are many copies of the processed pseudogenes.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies link ribosome protein mutations and abnormal ribosomes to poor prognosis, highlighting that ribosome protein targeted therapy is a promising treatment for cancer patients [ 11 ]. Ribosomal protein genes have the largest number of processed pseudogenes, approximately 1700; these genes include cyclophilin A, actin, keratin (keratin), GAPDH, cytochrome C (cytochrome C), and nucleophosmin [ 12 ]. There are many copies of the processed pseudogenes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RPS27A is responsible for the structural constituent of ribosomes, protein binding, and metal ion binding for MF. As RPS27A is a ribosomal protein, it regulates ribosome functions, especially protein synthesis and translation (Lari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dysregulation of RPS27A can cause alteration in ribosome functions, aberrant synthesis of protein, and high production of inflammatory cytokines which can eventually lead to damage in joint tissues in RA (Lari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Rong et al [ 34 ] found that iron death may affect AS through potential molecular regulatory pathways. In addition, ribosome-related genes and N6-methyladenosine RNA methylation regulators were also found to be dysregulated in AS [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%